The Role of Kindergarten Teachers in Instilling Moral Values in Pelangi Kindergarten Students, South Tangerang - Yulianti Fiyul, Arfiani (The International Journal of Education Management and Sociology, 2025)
This study aims to analyze the role of Kindergarten teachers in instilling moral values in Kindergarten of Pelangi Student, South Tangerang, and to identify the challenges faced by teachers in carrying out this role. The research employs a qualitative descriptive approach. Data was collected through observation, interviews, and documentation. The findings indicate that the role of Kindergarten teachers in instilling morals in early childhood at Pelangi Kindergarten includes: As a guide, the teacher provides direction to the children by engaging in direct conversations with polite and gentle language. As a coach, the teacher instills values and norms through repetitive practices and training. As a motivator, the teacher encourages the children by praising them and stimulating their interest with activities that engage them. As an inspirer, the teacher sets a good moral example through visual media, picture stories, or by being a direct role model. As an evaluator, the teacher assesses the children's morals using checklists and anecdotal notes, along with specific criteria that align with the assessment standards for early childhood. The challenges faced by teachers include internal factors, such as the differences in children's personalities, with some being very quiet and others highly active, and external factors, such as the lack of supportive family upbringing and a community environment that does not provide good moral examples.